2017
DOI: 10.1097/md.0000000000007606
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of Saussurea lappa extract via dual control of apoptosis and autophagy in prostate cancer cells

Abstract: To demonstrate the mechanisms of the curative effect of Saussurea lappa ethanol extract (SLE) against prostate cancer, we evaluated the effect of SLE on the induction of apoptosis and autophagy and investigated whether SLE-induced autophagy exerts a pro-survival or pro-apoptotic effect in lymph node carcinoma of the prostate (LNCaP) prostate cancer cells. SLE was prepared using 100% ethanol and added to LNCaP cells for 24 hours. Cell viability was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…MTT assay was used to assess cell proliferation and cell viability with respect metabolic reduction potential of the active cell. The effect of the prepared MgONPs on MCF-7 cell viability was examined at five different concentrations (20,40,60,80, and 100 μgmL -1 ) and time intervals (12, 24, 32, 48 and 60 h), respectively. Both the biosynthesized MgONPs induced MCF-7 cell cytotoxicity in a dose dependent manner.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…MTT assay was used to assess cell proliferation and cell viability with respect metabolic reduction potential of the active cell. The effect of the prepared MgONPs on MCF-7 cell viability was examined at five different concentrations (20,40,60,80, and 100 μgmL -1 ) and time intervals (12, 24, 32, 48 and 60 h), respectively. Both the biosynthesized MgONPs induced MCF-7 cell cytotoxicity in a dose dependent manner.…”
Section: Plos Onementioning
confidence: 99%
“…In the traditional folk medicine roots of S. costus are used as an ethnomedicine to cure indigestion, analgesic, abdominal pain, anthelmintic, dyspepsia, fever, and bronchitis [18]. The extracts and isolated macromolecules of S. costus are reported to exhibit antimicrobial [19], anticancer [20], antidiabetic and antilipidemic [21], anti-hepatotoxic [22] and anti-inflammatory [23] properties. Phytochemically, it contains sesquiterpenes, alkaloids, triterpenes, lignans, and tannins as the main bioactive constituents [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer cells, autophagy is triggered in response to cellular stress, such as nutrient or growth factor starvation and hypoxia (32). The occurrence of autophagy can inhibit tumor cell development in a number of tumors, such as osteosarcoma and glioblastoma (33,34). Further studies have demonstrated that autophagy is also closely related to tumor invasion and metastasis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…It is also considered as an anti-cancer herb. Recent studies have shown that the ethanol extract of Aucklandia lappa Decne has anti-cancer effect on prostate cancer, oral cancer, breast cancer, and cervical cancer [10][11][12]. In addition to its anti-tumor chemo-preventive effect, Costunolide also has anti-cancer activity against various cancer cells such as lung cancer, breast cancer, and liver cancer, and can inhibit the invasion and metastasis of cancer cells [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%